Síntese e investigação da atividade citotóxica de complexos de rutênio (II) contendo nicotinamida ou óxido nítrico e derivados piridínicos - Vieira, Henrique Vieira Reis Silva (2023)
The present work describes the synthesis, characterization, and in vitro study of the cytotoxic activity of six new ruthenium (II) phosphine complexes containing nicotinamide or nitric oxide and pyridine ligands in tumor cell lines MCF-7, HepG2, A549, SK-MEL-147, WM1366, and CHL-1 (breast adenocarcinoma, hepatocellular carcinoma, lung adenocarcinoma, and melanoma, respectively). Series 1 consists of three compounds with the following formulae: [RuCl(NIC)(dppb)(4,4'-Me-bipy)]PF6 (C1), [RuCl(NIC)(dppb)(4,4'-Methoxy-bipy)]PF6 (C2), and [RuCl(NIC)(dppb)(5,5'-Me-bipy)]PF6 (C3), where NIC = nicotinamide; dppb = 1,4- bis(diphenylphosphino)butane; 4,4'-Me-bipy = 4,4'-dimethyl-2,2-bipyridine; 4,4'-Methoxy- bipy = 4,4'-dimethoxy-2,2'-bipyridine; 5,5'-Me-bipy = 5,5'-dimethyl-2,2-bipyridine. Series 2 comprises three new nitrosyl complexes with pyridine ligands of the general formula [RuCl2(NO)(dppb)(L)]PF6, where L = pyridine (Py) (C4), 4-methylpyridine (4Pic) (C5), and 4-vinylpyridine (4VPy) (C6). The compounds were characterized by molar conductivity, elemental analysis, 1H, 13C{1H}, and 31P{1H} nuclear magnetic resonance spectroscopy, absorption spectroscopy in the infrared (IR) and ultraviolet-visible (UV-Vis) regions, mass spectrometry (series 1), cyclic voltammetry, polycrystalline, and single-crystal X-ray diffraction for (C1) and (C5). The stability in solution of the series 1 complexes in different solvents, namely dimethyl sulfoxide, methanol, ethanol, and dichloromethane, was evaluated. It was observed that the coordinated nicotinamide linker undergoes elimination of a carbamate group depending on the solvent evaluated. As for series 2, isomerization and subsequent coordination of the solvent (DMSO) were observed. The in vitro assays showed greater cytotoxic activity for C3 (IC50 = 18.06 ± 0.77 μM) compared to cisplatin (IC50 = 94.59 ± 3.95 μM) in the CHL-1 (melanoma) cell line. Furthermore, complex C3 inhibited the clonogenic ability and cell cycle progression of CHL-1 cells in the G0/G1 phase and induced apoptosis (programmed cell death) involving the production of reactive oxygen species (ROS). Finally, C3 demonstrated to act as a prodrug, generating the species [RuCl(Py)(dppb)(5,5'-Me- bipy)]PF6 under the conditions evaluated in the in vitro assays. The series 1 complexes demonstrated strong interaction with DNA (Kb = 106 L·mol-1 ) and weak to moderate interaction with human serum albumin (HSA).